2020
DOI: 10.1093/biolre/ioaa034
|View full text |Cite
|
Sign up to set email alerts
|

hCG Improves Luteal Function and Promotes Progesterone Output through the Activation of JNK Pathway in the Luteal Granulosa Cells of the Stimulated IVF Cycles†

Abstract: Human chorionic gonadotropin (hCG) is a luteotropic hormone that promotes the survival and steroidogenic activity of corpus luteum (CL) by acting through luteinizing hormone receptors (LHRs) expressed on luteinized theca and granulosa cells (GCs). Therefore, it is used to support luteal phase in in vitro fertilization (IVF) cycles to improve clinical pregnancy rates and prevent miscarriage. However, the molecular mechanism underlying this action of hCG is not well characterized. To address this question, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…We recently showed that hCG-induced improvement in luteal function is associated with activation of JNK pathway. When JNK pathway was inhibited pharmacologically or knocked-down with siRNA luteal function was compromised and P 4 production declined along with the expression of StAR and 3β-HSD in the cells 24 . It is worthwhile to note that the observed changes in the steroidogenic function of luteal GCs after JNK inhibition either pharmacologically or via siRNA are similar to those we observed after activin-A treatment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently showed that hCG-induced improvement in luteal function is associated with activation of JNK pathway. When JNK pathway was inhibited pharmacologically or knocked-down with siRNA luteal function was compromised and P 4 production declined along with the expression of StAR and 3β-HSD in the cells 24 . It is worthwhile to note that the observed changes in the steroidogenic function of luteal GCs after JNK inhibition either pharmacologically or via siRNA are similar to those we observed after activin-A treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Limited data is available on the biological role of this pathway in human ovary. We previously documented the critical roles of JNK pathway in the regulation of FSH induced follicle growth and cell cycle progression of granulosa cells in mouse model 29,30 , in the pathogenesis of granulosa cell tumor in human 31 , and very recently in the hCG-induced improvement of luteal function in human luteal GCs 24 . Albeit not human a study on rat ovary and granulosa cells demonstrated that the expression patterns of Jun and Fos family members in response to FSH and LH were distinct.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations